MUHAMMADIYAH TV SUSTAINABILITY VISION DESIGN PERSPECTIVE OF AL MAUN THEOLOGY - Eksanti; Luqman Hakim; M Irfan Tarmizi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Vision becomes a form or picture of what the company will be like. Vision can also be said to be the purpose of a company, so that the selection of vision can affect the form of business and the results that will be obtained from the business.